Negative body image evaluations in young adolescent boys and girls : assessing an integrative aetiological model - Kierans, Joanne (Trinity College (Dublin, Ireland). School of Psychology, 2014)
The present study provides a unique and timely contribution to Irish and international research focusing on one of the key concerns recently highlighted by young people in this country, that of body image. Recent prevalence rates in Ireland and other Western nations have highlighted the abundance of young people experiencing body image concerns, and research is continually indicating the negative implications of these concerns for adolescent mental health and associated behavioural outcomes. Consequently, the present research was conducted to provide a greater understanding of the range and patterns of social and individual level factors that influence negative body image evaluations in early adolescence.
Keywords: Psychology, Ph.D.; Ph.D. Trinity College Dublin